Foveal Phase Retardation Correlates With Optically Measured Henle Fiber Layer Thickness - Yuhas, Phillip T.; Ciamacca, Marisa L.; Ramsey, Keith A.; Mayne, Danielle M.; Stern-Green, Elizabeth A.; Ohr, Matthew; Zimmerman, Aaron; Hartwick, Andrew T. E.; VanNasdale, Dean A. (Frontiers in Medicine, 2022)
This study quantified and compared phase retardation distribution in the central macula with the thickness of the Henle fiber layer (HFL). A scanning laser polarimeter (SLP) was used to acquire 20° x 40° macular-centered images, either with fixed corneal compensation or with variable corneal compensation, in two cohorts of clinically normal subjects (N = 36). Phase retardation maps from SLP imaging were used to generate a macular cross pattern (fixed compensation) or an annulus pattern (variable compensation) centered on the macula. Intensity profiles in the phase retardation maps were produced using annular regions of interest at eccentricities from 0.25° to 3°. Pixel intensity was averaged at each eccentricity, acting as a surrogate for macular phase retardation. Directional OCT images were acquired in the horizontal and vertical meridians in all subjects, allowing visualization of the HFL thickness. HFL thickness was manually segmented in each meridian and averaged. In both cohorts, phase retardation and HFL thickness were highly correlated in the central 3° assessed, providing further evidence that the source of the phase retardation signal in the central macula is dominated by the HFL and that the center of the macula on cross sectional imaging corresponds closely with the center of the macular cross on SLP imaging.